The great recession and mental health: The effect of income loss on the psychological health of young mothers - Fiona Kiernan (University College Dublin, UCD School of Economics, 2018)
There is little consensus as to the effect of recessions on health, which may be due to the heterogenous nature of recessions, the choice of health outcome or the description of the independent variable involved. In contrast to previous work, which has predominantly studied labour market loss, I examine the relationship of income loss and health, and in particular focus on psychological rather than physical health. I study disposable income loss because disposable income is related to consumption expenditure, and therefore satisfaction. Psychological, rather than physical, health is important because younger populations are unlikely to manifest clinical evidence of recession-related disease in the short term. The Irish recession provides me with an opportunity to study the effect of changes in income, since households who remained in employment also experienced changes in disposable income. Using panel data from three waves of the Growing Up in Ireland study, I find that income loss is associated with an increase in depression, but not in parental stress. This effect of income loss is seen for those who are home owners, and subjective reports of being in mortgage or rent arrears is also associated with an increase in depression score.
Keywords: 330